Alternatives to cash prices in fed-cattle price discovery - Mintert, J.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Price discovery in fed cattle markets is a significant concern as cash market volume declines and trade becomes more sporadic. Producers need to consider other sources of pricing information when negotiating cash trade and long-term marketing agreements. This study evaluated several alternative price sources for producers to consider. Live cattle futures and wholesale boxed-beef prices offer the most promise; however, both also have limitations associated with their use.
Keywords: Beef; Cattle price discovery; Futures markets; Wholesale beef prices